DGet! An open source deuteration calculator for mass spectrometry data - Thomas E. Lockwood; Alexander Angeloski (Journal of Cheminformatics, 2024)
Abstract DGet! is an open-source analysis package written in Python for calculating the degree of deuterium enrichment in isotopically labelled molecules using mass spectrometric data. The nuclear properties of deuterium make it a valuable tracer in metabolic studies and an excellent contrast agent in nuclear spectroscopies. Determination of molecular deuteration levels is typically performed using mass spectrometry, however software options to perform these calculations are scarce. The in-house scripts and spreadsheets currently used rarely account for isotopic interferences from 13C or multi-isotopic elements that impact deuteration calculations. DGet! removes isotopic interferences using de-convolution and both the isotopological makeup and overall deuteration level can be accurately recovered. The software is available as command line and web applications that take a molecular formula and mass spectrometry data and output a graphical representation of the degree of deuteration as well as the distribution of partially deuterated analogues. These applications are designed to be easy to use and enable superior characterisation of deuterated molecules for users of all levels of expertise, without the limitations of techniques currently used by the majority of deuteration laboratories and researchers. Graphical Abstract